An In-Depth Analysis of Credit Risk: Taking Proactive Measures to Tackle Non-Performing Loans in the Banking Sector - Wijoyo, Tuwuh Adhistyo; Apriyani, Eka (Jurnal Mantik, 2024)
Banking distributes savings to borrowers, boosting economic activity. Recent Bank Indonesia (BI) data reveals a troubling trend of falling credit quality and growing NPLs in the industry. The global financial crisis, market competitiveness, and lax lending laws impact this. Banks' reluctance to adjust interest rates during economic uncertainty has increased businesses' repayment responsibilities despite decreasing income. Non-performing loans have grown unintentionally as regulators lower collateral and deposit restrictions to improve credit distribution. In this case, proactive credit restructuring is advocated. Reduce non-performing loans and stabilise banks. Banks use credit restructuring to help distressed debtors fulfil their obligations while safeguarding loan loss reserves. Effective credit management decreases loan risks and involves stakeholders. Qualitative descriptive study examines credit management techniques and challenging loan frequency. The results emphasise the necessity for strict credit standards, strong monitoring systems, and resolutions including restructuring loans and selling assets to reduce non-performing loan risks. Regulators, banks, and other stakeholders must collaborate to address NPLs and stabilise finances. Active credit management may assist banks manage NPLs and maintain economic development.